The effectiveness of clt techniques to develop speaking skills in 6th grade students from Marco Aurelio Subía Martinez educative unit - Canchig Chicota, Juan Carlos (2023)
Nowadays, globalization has led to make countries use English language to communicate for different purposes. The dominance of this language has changed the way of many areas. It is the case of studying a foreign language in which it is not only essential to understand the sentence structure rather than how to use the language in an appropriate context, which allows learners to engage in the communication process. During the teaching of the English language, the strategies and techniques that are developed in the classroom have the purpose of allowing the development of the four skills that compose the learning of the English language. However, the primary skill that causes difficulties in developing is speaking. So, this research project aims to determine the effectiveness of Communicative Language Teaching Techniques for developing speaking skills in Marco Aurelio Subía Martinez Educative Unit from students of 6th "A" with 36 students. The researchers used a mix-method, both qualitative and quantitative approaches because the information was described in a discussion and shown in percentages. Also, it is a descriptive research and data collection was obtained through an interview and a survey. The results determined the effectiveness of Communicative Language Teaching techniques for developing speaking skills. On the other hand, the students showed a desire to maintain a learning process that involves activities that motivate collaboration within the classroom, as well as a collaborative work. Therefore, the effectiveness of the techniques based on Communicative Language Teaching for the development of speaking skills is recommended.